HR Competency Analysis on Increasing MSMEs Performance In Supporting Industrial Era 4.0 - Anis Anshari Mas'ud; Andi Putri Tenriyola (Jambura Science of Management, 2023)
Purpose: This study describes the analysis of human resource competencies in the era of the industrial revolution 4.0 in improving the performance of MSMEs. Technological and industrial developments require competent human resources in every organization.Design/Methodology/Approach: The research was conducted in several businesses in Parepare City, where the sample was determined by purposive random sampling. This research uses qualitative research methods that emphasize the process of understanding based on facts in investigating a social phenomenon and human problems and is presented analytically and descriptively, which has been collected and then interpreted systematically.Findings:The results of the research based on the qualitative approach conducted show that to achieve competent human resources in the era of the industrial revolution 4.0, human resources in companies are required to be adaptive, following company goals to adjust to employee profiles quickly, respond to the needs and developments of the times. Various challenges arise, especially related to the speed of adapting to change and the ability to collaborate virtually. The recommendations recommended in this study are to improve the performance of MSMEs as business actors to encourage the competence of the quality of human resources, especially in anticipating industry 4.0 to pay attention to and maximize aspects; Adaptive thinking and virtual collaboration.